ENHANCING SCIENCE LEARNING OUTCOMES THROUGH HUMAN RESPIRATORY ORGAN PUZZLE MEDIA AMONG FIFTH-GRADE STUDENTS AT SD NEGERI LAMREUNG, ACEH BESAR - Helminsyah Helminsyah; Tria Marvida (Lembaga Penelitian dan Pengabdian (LP2M) STKIP Bina Bangsa Getsempena, 2023)
This study aims to determine the effect of using Human Respiratory Organ Puzzle Media on improving science learning outcomes of fifth-grade students at SD Negeri Lamreung, Aceh Besar. The media was designed to help students understand respiratory organ concepts through enjoyable and contextual interaction. This research employed a quantitative approach with a quasi-experimental Pretest-Posttest Control Group Design, involving 40 students (20 control, 20 experimental). Data were collected through learning outcome tests and student response questionnaires, analyzed using t-tests. Validity test results showed all items were valid (r-count > r-table) and the instruments were reliable (Cronbach's Alpha > 0.60). Normality tests showed data were normally distributed (Sig. > 0.05). Paired Sample t-test results showed a significant difference between experimental and control classes with Sig. (2-tailed) = 0.000 < 0.05 and t = -15.515. These findings indicate that the Human Respiratory Organ Puzzle Media significantly improves learning outcomes, motivation, cooperation, and active engagement of students in elementary school science learning.